Mengukur Kelayakan Ekonomi Proyek Paperless Office Menggunakan Metode Cost & Benefits Analysis (Studi Kasus: Industri Garment) - Nancy Oktyajati; Sri Mayasari; Hardik Widananto (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2019)
This paper discusses the economic feasibility study of the project of procuring computer and tablet devices to companies as one part of the business in the paperless office. The purpose of this study is to analyze the feasibility of investment to increase productivity, reduce costs, improve site efficiency and reduce environmental impacts. Computer and tablet devices are used to reduce the cost of procuring documents which are usually carried out by the photocopy process and distributed to other departments. Measurement of investment feasibility using Cost and Benefit Ratio Analysis. The economic tools used in this investment feasibility study include Payback Period, Net Present Value (NPV), Return on Investment (ROI) dan Internal Rate of Return (IRR). The results of economic analysis using the cost benefit ratio method for the paperless office project are that the project deserves to be accepted.